Mothers at risk of postpartum depression in Sri Lanka: A population-based study using a validated screening tool. - Therese Røysted-Solås; Sven Gudmund Hinderaker; Lasantha Ubesekara; Vijitha De Silva (PLoS ONE, 2022)
Background Postpartum depression is an important public health concern. The prevalence of postpartum depression is estimated to be 18% worldwide. The purpose of this study was to estimate the prevalence of mothers at risk of postpartum depression in Sri Lanka and to investigate its associated risk factors. Methods This was a cross-sectional study conducted among 975 mothers in Galle district, Sri Lanka. The prevalence of mothers at risk of postpartum depression was assessed using the Edinburgh Postpartum Depression scale (EPDS) which has been validated for screening for mothers at risk of postpartum depression in Sri Lanka with a cut-off score 9 or more. Prevalence was estimated using a cut-off 9 or more, 10 or more, 11 or more and 12 or more to assess the difference in prevalence using unvalidated cut-offs for screening. Data from routine records on pregnancy, delivery and postnatal care was collected to investigate possible predictors of EPDS score 9 or more (risk of postpartum depression). Univariate and multivariable logistic regressions were performed to identify risk factors for EPDS score 9 or more (risk of postpartum depression). Results The prevalence of mothers with EPDS score 9 or more was found to be 9.4% (95%CI: 7.8-11.4); EPDS score 10 or more was 5.6% (95%CI: 4.4-7.3). EPDS score 9 or more (risk of postpartum depression) was associated with the following risk factors: Former history of mental illness (aOR 32.9, 95%CI: 7.9-136.2), high maternal age 30-39 (aOR 2.2, 95%CI: 1.3-3.8), BMI 25.0-29.9 (aOR 2.6, 95%CI: 1.5-4.5), hypertension (aOR 3.6, 95%CI: 1.2-10.9) and newborn death (aOR 28.9, 95%CI: 4.5-185.1). One in five women reported thoughts of self-harm. Conclusion Around one in ten mothers in Sri Lanka experience symptoms of postpartum depression, highest risk among mothers who reported former history of mental illness and newborn death. The prevalence estimates were lower with a higher cut-off for screening and this highlights the importance of using the validated cut-off for screening in future studies on postpartum depression in Sri Lanka. Mothers at increased risk should be identified in antenatal care and are important targets of referral.